Tourism students’ opinions on competencies and educational performance - Rodzuan, Abdul Adib Shah; Saad, Mazni (2019)
Educational institutions should provide and prepare the students with essential knowledge, individual skills as well as student's attitudes and behaviour which might help their educational performance. Students nowadays seem to have issues regarding their educational performances as most of the students do not meet fundamental competency required by the subjects or courses. Yet, their teachers and lecturers give them an exception to it. Besides that, Malaysian students still had a deficiency with the traits of leadership compared to international students. The respondents for this study are from the tourism students in International Islamic University Malaysia (IIUM), Pagoh, Johor as well as from Universiti Teknologi Mara (UiTM), Lendu, Melaka. The total response is 30 out of 50 questionnaires that have been distributed. The data were analyzed by using IBM SPSS version 21 and the outcomes of this study show the most important attributes that related with educational performances are the essential knowledge while the individual skills have been recorded as the most competencies need to be improved. Indirectly, it will give opportunities to the students and educational institutions to acknowledge the importance of competencies towards their students' performances.